2015
DOI: 10.1139/cgj-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

Axial monotonic and cyclic compression behaviour of hollow-bar micropiles

Abstract: Micropiles are used in various applications, including low-capacity micropile networks, underpinning, and seismic retrofitting of existing foundations and high-capacity foundations for new structures. Hollow-bar micropiles have an added advantage, as they provide fast installation with a high degree of ground improvement. The current Federal Highway Administration (FHWA) design guidelines designate hollow-bar micropiles as type B, even though the FHWA construction technique is different than the technique used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In practice, the Federal Highway Administration (FHWA) guidelines for micropile design and construction suggest the range of bond strength (α bond ) values at the pile-to-ground interface as the main factor for calculating the design capacity considering the grouting method (FHWA 2005). Several researchers have carried out various studies to derive high bond strength by modifying the construction method and the structure compositions of the pile to improve the bearing performance of the micropile compared to the conventional pile (Gomez et al 2008;Bennet and Hothem 2010;Drbe and El Naggar 2014;Abd Elaziz and El Naggar 2015;Vickars and Clemence 2000;El Sharnouby and El Naggar 2012;Papadopoulou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the Federal Highway Administration (FHWA) guidelines for micropile design and construction suggest the range of bond strength (α bond ) values at the pile-to-ground interface as the main factor for calculating the design capacity considering the grouting method (FHWA 2005). Several researchers have carried out various studies to derive high bond strength by modifying the construction method and the structure compositions of the pile to improve the bearing performance of the micropile compared to the conventional pile (Gomez et al 2008;Bennet and Hothem 2010;Drbe and El Naggar 2014;Abd Elaziz and El Naggar 2015;Vickars and Clemence 2000;El Sharnouby and El Naggar 2012;Papadopoulou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies indicated that the a bond values for type B, which correspond to the pressurized grouting characteristics of the hollow-bar micropile, can lead to underestimation of the bearing capacity of hollow-bar micropiles. Therefore, various follow-up studies have been performed to propose reasonable design parameters considering the in situ conditions of the hollow-bar micropile [1,4,6,11,24].…”
Section: Introductionmentioning
confidence: 99%
“…Load-displacement in the cycling direction is obtained from numerical analysis, using ABAQUS software [Figs. [5][6]. In comparison models 1 and 2, the loading, unloading and reloading cycles, show different shape for each model.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 98%
“…In the construction industry and related field, several characteristics of different structure, structural elements, substructure and construction materials are numerically, theoretically and experimentally reported in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], but little research has been done on timber structure design. A timber structure state of art has numerically been investigated, to understand seismic resistance by the evaluation of the load, displacement and stress have been applied on the timber structures [1].…”
mentioning
confidence: 99%